Pengaruh Return on Asset (ROA), Current Ratio (CR), Net Profit Margin (NPM) dan Inflasi terhadap Harga Saham (Studi Kasus PT Kalbe Farma, Tbk. Periode Tahun 2001–2014) - Subarjo Subarjo (Universitas Proklamasi 45 Yogyakarta, 2015)
This study wasconducted toexamine the effect ofROA, CR, NPM andinflationon the price of the shares of PT KalbeFarma. Thisresearchusescasestudyperiodof 2001-2014.The analysis usedis multiple regression withSPSS.From the results of the analysis indicate that the individual ROA CR, NPM and inflation affect the stock price of PT Kalbe Farma. While jointly ROA CR, NPM and inflation affect the stock price of PT Kalbe Farma.